Pengaruh Brand Awareness dan Online Customer Review Terhadap Minat Beli Merek Adidas Pada Pengguna Shopee di Indonesia - Muhammad Firli Musaffa; Budi Prasetiyo (FEB Universitas Maritim Semarang, 2025)
This research investigates the impact of brand awareness and online customer reviews on purchase intention regarding Adidas products on the Shopee platform in Indonesia. The research background is founded on the growth of e-commerce and the intense competition present in Indonesia’s fashion industry. A quantitative method employing a survey approach was utilized, engaging 150 Shopee users who are familiar with Adidas products. Data analysis encompassed descriptive tests, classical assumption tests, multiple linear regression, hypothesis testing, and the coefficient of determination, all performed using SPSS version 27. The results demonstrate that brand awareness and online customer reviews have a positive and significant effect on consumer purchase intention, both individually and collectively. These findings imply that greater brand awareness and the quality of reviews are associated with an increase in purchase intention for Adidas products on Shopee. This research offers insights for Adidas Indonesia regarding the significance of enhancing brand awareness and fostering authentic reviews through exclusive promotions, review incentives, and the use of the “Verified Purchase” feature. Future research should be encouraged to integrate additional variables such as price and product quality for a more comprehensive analysis